Inmates' Wives' Unusual Dedication at Nigeria's AgodiIbadan Medium Correctional Facility - Adetunji, Christian Matthew; Kamau, Elizabeh Wangui; Wambugu, Anne Gathoni (European Scientific Journal, ESJ, 2023)
This research set out to explain how inmates wives perceived the phenomenon of their incarcerated partners. The research used the personal iceberg metaphor model of Satir and interpretative phenomenology analysis to understand the lived experiences of ten non-incarcerated partners at Nigeria's Agodi-Ibadan medium correctional facility. According to the findings, the non-incarcerated partners believed their partners were not guilty of the offense that was brought against them. They also thought that society made incorrect judgments about their partners. Additionally, they believed that God had approved of their spouses' incarceration. Their co-parenting, interpersonal relationships, physical and emotional health, and socioeconomic situation were all impacted by these opinions. The research offered counseling professionals a few recommendations.